Salacca sumatrana - based project-based learning: Students' positive attitudes and critical thinking - Fitri Agustina Lubis; Yus Mochamad Cholily; Abdulkadir Rahardjanto; Yuni Pantiwati; Poncojari Wahyono (University of Muhammadiyah Malang, 2025)
The aim of this research is to determine the relationship between learning models Project-Based Learning (PjBL) and the local potential of South Tapanuli for positive attitudes and critical thinking skills of students. The research method uses Systematic Literature Review (SLR) assisted by Google Scholar and Publish or Peris, with data analysis techniques using PRISMA. The conclusion from SLR, research using all variables has never been studied. However, PjBL in the learning process, based on previous research, has several advantages, such as increasing students' positive attitudes, students' learning motivation, increasing students' ability to learn cooperatively and collaboratively, increasing students' creativity, increasing students' academic abilities, improving students' communication skills. Because students are required to work with other people, improve problem solving abilities, management abilities, and the ability to coordinate learning resources, as well as creating a pleasant learning environment. The implications of this research emphasize the importance of utilizing local resources in learning to foster engagement and high-level thinking skills in students.